A distribuiç\~ao de profissionais técnico-científicos pelo território Brasileiro em 2000 e 2010 - Aguinaldo Nogueira Maciente; Rafael Henrique Moraes Pereira; Paulo A. Meyer M. Nascimento (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– This article describes the distribution of Science, Technology, Engineering and Mathematics (STEM) graduates in Brazil according to meso-regions of the 2000 and 2010 population censuses. Changes in the geographic distribution of these professionals over this period are presented, as well as the regions of the country that have a higher concentration of these professionals. Results show that STEM graduates became increasingly concentrated in high-income meso-regions of the South and Southeast in and in the metropolitan regions of the Northeast and North. These professionals show a greater tendency to work as formal-market employees and employer entrepreneurs, relative to other higher-education professionals, who are more likely to work in the informal market or work as non-employing small entrepreneurs. Construction, mining and information-technology industries have the highest percentages of STEM workers among higher-education personnel, and are also the industries in which these workers are more likely to work in typical STEM field occupations.
Keywords: R23; 330; STEM graduates; human capital concentration; job market for skilled labor